2017
DOI: 10.1007/s00264-017-3699-4
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage revision of infected shoulder arthroplasty using prosthesis of antibiotic-loaded acrylic cement: minimum three-year follow-up

Abstract: Using PROSTALAC in two-stage revision arthroplasty is effective for infection control and produced good clinical outcomes after second-stage shoulder re-implantation. However, cases involving segmental bone defects require additional precautions in maintaining the appropriate tension and height to prevent complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…A total of 712 studies were found through the electronic search and 14 studies were added after cross-referenced research on the bibliography of the examined full-text articles. After a preliminary analysis, a total of 24 studies were included in this systematic review [13][14][15][16][17][18][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] (Table 2, Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 712 studies were found through the electronic search and 14 studies were added after cross-referenced research on the bibliography of the examined full-text articles. After a preliminary analysis, a total of 24 studies were included in this systematic review [13][14][15][16][17][18][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] (Table 2, Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen series reported on shoulder PJI treated with two-stage protocol, [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] 4 studies reported on shoulder PJI treated with single-stage protocol, [13][14][15][16] while in two series both series of single-and two-stages protocols were reported. 17,18 Five studied were retrospective comparative cohort studies, 14,18,34,36,37 19 studies were retrospective case series.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of PSI after primary shoulder arthroplasty is estimated to be 1 to 5%, depending on the study; after revision surgery, however, the incidence can reach 15% [49, 55]. Operative approaches including debridement, antibiotics, and implant retention (DAIR) and one- and two-stage revision surgery have been used over the years, but the debate over which is the best for managing this disabling condition is still open [10, 27, 28].…”
Section: Introductionmentioning
confidence: 99%